Rural Saving Mobilizations and Economic Development in Akamkpa Local Government Area of Cross River State - Nigeria - Ekpung, Edame Greg; Udude, Celina Chinyere; Etim, Bassey Samuel (Journal of Challenges, 2015)
This study presents an analysis of “Rural Saving Mobilizations and economic development in Akamkpa Local Government Area of Cross River State Nigeria”. The data available shows that savings mobilization plays an important role in rural development and in rural Economy like Akamkpa Local Government Area of Cross River State Nigeria. The major objectives of the study are to examine the mobilization of rural savings in Akamkpa Local Government Area of Cross River State and the factors militating against the mobilization of savings in the area. The study also assesses the roles and contributions of the formal and informal financial sectors in the mobilization of savings from the rural area. Primary and secondary data were collected from the rural households and the two major financial institutions in the area then (the Union Bank of Nigeria Plc, and the peoples Bank of Nigeria). The analysis shows that 80% of Awi- the Cross River State College of education Community indicated a greater percentage of their awareness to save their money in the bank. It was also discovered that out of 351 workers of the State college of Education, Akamkpa, 243 or 69.23% save with the Union Bank of Nigeria, Akamkpa Branch under the salary payroll Accounts. While 108 or 30.77% save with the people Bank of Nigeria, Akamkpa branch respectively. The study also reveals that the higher the rate of interest, the greater the inducement to Savers to increase their savings and supply more funds. policy implications of the study are that the government or the monetary authority should maintain the equality of saving and investment where the market rate of interest equal to the natural rate.